2019
DOI: 10.3390/su11041032
|View full text |Cite
|
Sign up to set email alerts
|

Trade Credit Financing and Sustainable Growth of Firms: Empirical Evidence from China

Abstract: As an effective substitute for bank credit to ease financing constraints, trade credit plays an important role in the operation and growth of enterprises. This paper extends the literature by providing evidence on the relationship between trade credit financing and firm-level sustainable growth. Using the financial statement data of 20,089 Chinese A-share listed firms over the period 2003 to 2017, running a regression using the cross-section regression method and employing the two-stage instrumental-variable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
(86 reference statements)
6
30
0
Order By: Relevance
“…A similar relationship between the use of trade credit and profitability stems from S. Kumaraswamy and S. George's research, and the authors argue that effective debt management helps improve cash flow in an enterprise [23]. In turn, research on the Chinese market showed that the use of trade credit also had the significant impact on the sustainable development of enterprises, especially those with greater internal control capabilities [24]. In general, trade credit seems to increase the efficiency of enterprises, especially those that are more exposed to financial restrictions, i.e., smaller and younger enterprises, and thus contributes to reducing these restrictions [25].…”
Section: Introductionmentioning
confidence: 77%
“…A similar relationship between the use of trade credit and profitability stems from S. Kumaraswamy and S. George's research, and the authors argue that effective debt management helps improve cash flow in an enterprise [23]. In turn, research on the Chinese market showed that the use of trade credit also had the significant impact on the sustainable development of enterprises, especially those with greater internal control capabilities [24]. In general, trade credit seems to increase the efficiency of enterprises, especially those that are more exposed to financial restrictions, i.e., smaller and younger enterprises, and thus contributes to reducing these restrictions [25].…”
Section: Introductionmentioning
confidence: 77%
“…As such, although younger firms rely more heavily on trade credit, it also plays a key role for older firms, which may reflect a preference towards older SMEs due a relationship of trust built up by suppliers over the years. The impact of trade credit on a variable representing the 'sustainable growth of the firm' (longterm profitability and lasting competitiveness without exhausting the firm's financial resources) has been investigated recently [118] on a sample of Chinese A-share private listed companies from 2003 to 2017. The findings were that trade credit plays an important role in accelerating the search for sustainable growth, particularly for firms with a higher level of internal control quality, and that in areas with a lower (higher) financial competition, the contribution of trade credit to the sustainable growth of the firm is stronger (weaker).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies show that a trade credit (granted and received) is directly correlated with the size of an enterprise, and with return on capital, while negatively correlating with return on assets (Bărbuţă-Mişu, 2019). The literature also indicates that a trade credit may have a positive impact on the sustainable development of an enterprise (Huang et al, 2019;, on innovative activity of an enterprise (Khovrak, 2013), as well as increase the efficiency of business operations and help reduce financial constraints (Agostino & Trivieri, 2019). However, offering a trade credit requires skillful management of receivables in the enterprise (Zimon et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%